The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1016/0092-8674(90)90291-l
|View full text |Cite
|
Sign up to set email alerts
|

Reduced DNA polytenization of a minichromosome region undergoing position-effect variegation in Drosophila

Abstract: SummaryMolecular analysis of a Drosophila minichromosome, Dp(1;f)1187, revealed a relationship between position-effect variegation and the copy number reductions of heterochromatic sequences that occur in polytene cells. Heterochromatin adjacent to a defined junction with euchromatin underpolytenized at least 60-fold. Lesser reductions were observed in euchromatic sequences up to 103 kb from the breakpoint. The copy number changes behaved in all respects like the expression of yellow, a gene located within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 43 publications
3
73
0
1
Order By: Relevance
“…Pulsed-field electrophoresis and Southern blot hybridization: Salivary gland nuclei isolated from the third instar larvae were embedded into agarose and DNA was treated in agarose inserts as described in Karpen and Spradling (1990). The DNA samples were digested with NotI and fractionated by contour-clamped homogeneous electric field pulsed-field gel electrophoresis on a Bio-Rad (Hercules, CA) DRII apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsed-field electrophoresis and Southern blot hybridization: Salivary gland nuclei isolated from the third instar larvae were embedded into agarose and DNA was treated in agarose inserts as described in Karpen and Spradling (1990). The DNA samples were digested with NotI and fractionated by contour-clamped homogeneous electric field pulsed-field gel electrophoresis on a Bio-Rad (Hercules, CA) DRII apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…After pulsed-field gel electrophoresis, DNA was transferred to the Hybond-N filter (Amersham-Pharmacia-Biotech) and analyzed by Southern blot hybridization as described earlier (Karpen and Spradling 1990).…”
Section: Methodsmentioning
confidence: 99%
“…These observations and model are consistent with a previous report of heterochromatic repair foci in endocycle cells of the ovary (Hong et al 2007). In fact, previous analyses had indicated that these chromatin junctions are fragile in the endocycle, and that fragility correlates with the degree of underreplication (Karpen and Spradling 1990;Leach et al 2000;B. Calvi, unpubl.).…”
Section: Damage At Chromatin Junctions In Both Normal and Rereplicatimentioning
confidence: 99%
“…The antisense RNA model also cannot easily account for the chromosome-local nature of the phenomenon demonstrated here, nor for the persistence of dominant variegation following complete excision of the entire wild-type brown gene from which antisense RNA is presumably made. A somatic gene loss model for position-effect variegation, originally proposed by Schultz and recently reformulated by Karpen and Spradling, also does not easily account for dominant variegation (Schultz 1936;Karpen and Spradling 1990). If gene loss were responsible for the variegation in V21, it is difficult to see how V21[P(Abw)] deletions could lead to suppressed phenotypes in a size-dependent manner.…”
Section: Active Inactivementioning
confidence: 99%